2018
DOI: 10.3390/polym10090957
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Production of Polyhydroxyalkanoates from Waste Polystyrene Fragments Attained Using Oxidative Degradation

Abstract: Excessive levels of plastic waste in our oceans and landfills indicate that there is an abundance of potential carbon sources with huge economic value being neglected. These waste plastics, through biological fermentation, could offer alternatives to traditional petrol-based plastics. Polyhydroxyalkanoates (PHAs) are a group of plastics produced by some strains of bacteria that could be part of a new generation of polyester materials that are biodegradable, biocompatible, and, most importantly, non-toxic if di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 48 publications
2
63
0
Order By: Relevance
“…To analyze the nature of the oxidized groups in more detail, FTIR was applied. The increase in acid number after oxidation treatments indicated the presence of aldehyde, ketone, or carboxylic acid groups [17,20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the nature of the oxidized groups in more detail, FTIR was applied. The increase in acid number after oxidation treatments indicated the presence of aldehyde, ketone, or carboxylic acid groups [17,20].…”
Section: Resultsmentioning
confidence: 99%
“…A disadvantage of using shake flasks is that conditions monitoring is limited, however, for the purposes of this study, the required parameters were maintained. The oxidatively prodegraded PP fermentation, herein described, could be one way according to which plastic solid waste (PSW) could be recycled for value-added PHA productions [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely recognized microbial PHA is poly 3- hydroxybutyric acid (PHB), a homopolymer of 3-hydroxybutyrate. This homopolymer is brittle and biodegradable and thermoplastic; however, only limited industrial use owing to high production cost of PHB is reported till date ( Reis et al., 2008 ; Johnston et al, 2018 ).…”
Section: Production Of Biopolymers From Different Food Wastesmentioning
confidence: 99%
“…The fact that the isolate is a Gram-positive bacterium can be considered being very beneficial. Most of the currently used PHA-producing strains are Gram-negative bacteria such as Cupriavidus necator [20,21], transgenic Escherichia coli [22] or members of the genus Halomonas [23,24]. Actually, one of the major obstacles preventing application of PHA in high-value applications such as health care, cosmetics or medicine is the fact that the polymers isolated from Gram-negative strains are heavily contaminated by lipopolysaccharides (LPS), a group of endotoxins produced by Gram-negative bacteria as important component of their outer cell membrane.…”
Section: Taxonomic Metabolic and Morphological Description The Isolatementioning
confidence: 99%